If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 70 + -20 + y + 10 = 0 Reorder the terms: 70 + -20 + 10 + y = 0 Combine like terms: 70 + -20 = 50 50 + 10 + y = 0 Combine like terms: 50 + 10 = 60 60 + y = 0 Solving 60 + y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-60' to each side of the equation. 60 + -60 + y = 0 + -60 Combine like terms: 60 + -60 = 0 0 + y = 0 + -60 y = 0 + -60 Combine like terms: 0 + -60 = -60 y = -60 Simplifying y = -60
| 18+-1n=10 | | -3(-3)+2(-3)-3=0 | | 34xn=34 | | 3[d+12]=8-4d | | 9(-9)-10(-9)+9=0 | | (9)9-10(9)+9=0 | | -5x+3=6x-2 | | 9+9=(5+4m) | | 39/n=3 | | x+(x*0.06)=50 | | x^3-x^2-32x+60=0 | | f(x)=tanh(7x) | | 9s-10t=2 | | y=1000X | | (16x^4)+(32x^3)-(8x^2)-24x+9=0 | | 2/5=8 | | z^10=-1+i | | 12t-4.9t^2=5 | | (6×2)/3 | | y=10*ln-6*ln*x+ln*x^2 | | (22x-30)=(15x+19) | | 4x=120-1/4 | | 2(3y-6)=29 | | 2x^2+19x+13=0 | | 4a-2=8 | | 34+78=31 | | 1/4(3x-16)=1/4x=16/3 | | 3x+-5y=40 | | y^2-6y-39=0 | | -7(2t+7)=-119 | | 5(f-3)=-25 | | 10(s-9)=-156 |